Workplace wellness strategies for small businesses. Issue 1 (6th February 2017) - Rucker, Michael Raymond
Abstract : Purpose: The purpose of this paper is to identify strategies used within small- to mid-size organizations that run effective workplace wellness programs, and remedy a current research gap that exists in the available academic literature regarding this topic. Design/methodology/approach: Data were collected from four organizations in the form of case studies. Similarities, differences and patterns between different cases were explored, and thematic analysis was used to identify and explain meaningful commonalities between the programs studied. Findings: The analysis revealed five overarching common concepts: innovation, company culture, employee-centric, environment, and altruism. Under these five concepts, 19 common themes were identified that represent common workplace wellness strategies. Research limitations/implications: A relatively small number of participants were included in the study, which could be viewed as a limitation of the qualitative approach. Practical implications: This study identified several strategies used by small- to mid-sized businesses (SMBs) with effective and viable workplace wellness programs and could help inform the practices of other small businesses. The study's findings could also be applied to broader theory in organizational and social psychology. Social implications: Strategies from this study potentially could be used to help improve the well-being of employees in SMBs. Originality/value: The study challenges some of the established views on workplace wellness and provides a better understanding of the unique attributes of successful SMB programs, especially when compared to the attributes of workplace wellness programs operating in larger enterprises.